Radiosynovectomy is a safe and an efficient alternative in the treatment of chronic, recurrent knee hemarthrosis - Ioannis Iakovou; Dimitrios Kotrotsios; Konstantinos Michailos; Christos Sachpekidis (World Journal of Nuclear Medicine)
Chronic recurrent hemarthrosis, defined as repeated intra-articular hemorrhage, can lead to a disabling arthropathy. We herein report on a 26-year-old patient presenting with recurrent, postoperative, serious knee hemarthrosis refractory to conventional treatment, including systemic and intra-articular steroid injections as well as chemical synovectomy with osmic acid. The patient was finally treated with a twice performed knee radiosynovectomy with yttrium-90 and showed an extraordinary good clinical outcome with a symptom-free period of 4 years. In cases of refractory hemarthrosis, radiosynovectomy should have a place in the therapeutic armamentarium of the treating physician, as a minimally invasive, safe, and efficient therapeutic tool.